A vehicular ad hoc network privacy protection scheme without a trusted third party - Wang, Xiaoliang; Li, Shuifan; Zhao, Shujing; Xia, Zhihua; Bai, Liang (International journal of distributed sensor networks, 2017)
Vehicular ad hoc networks are traffic applications of the Internet of Things, which are composed of vehicle nodes, roadside units, service providers, and other components. In a vehicular ad hoc network, data transmission and management rely heavily on the wireless channel, which is subject to potential threats such as information leakage and data attacks due to the openness of the automotive network. The construction of a secure and trusted system that does not damage the privacy of vehicular ad hoc networks must be further addressed. Existing works usually focus on the anonymous authentication mechanism but neglect anonymity abuse. Furthermore, they always require a trusted third party as a central authority, which causes some security problems. In view of these problems, this article proposes a scheme that is based on the no-certificate-center algorithm. By security analysis and experiments, the scheme is proved to have higher anonymity and higher efficiency.